Insecticidal activity of essential oil from Eucalyptus globulus against Aphis nerii (Boyer) and Gynaikothrips ficorum (Marchal) - Russo, Serafina (2018)
Fil: Russo, Serafina. Universidad de Buenos Aires. Facultad de Agronomía. Buenos Aires, Argentina.